Teeth roots displacement in the maxillary sinus: characteristics and management - Seigneur Mathilde; Cloitre Alexandra; Malard Olivier; Lesclous Philippe (EDP Sciences, 2020)
Introduction: Teeth displacement in the maxillary sinus is one of the most frequently described peri-extraction complications in oral surgery. Roots or whole teeth accidentally displaced during an avulsion process are the most common cause of foreign bodies in the maxillary sinus. It exposes the patient to more or less serious complications that can go as far as development of pneumonia or septic thrombosis of the cavernous sinus in rare cases. Several therapeutic solutions can be proposed to manage this complication, ranging from therapeutic abstention to the removal of the dental component using various techniques. Corpus: The pedagogical objectives of this article are to explain the main characteristics of this complication as well as its treatment. Through a systematic review of the literature according to the PRISMA methodology, the risk factors, prevention, diagnosis, complications, and management of teeth displacement will be discussed. A treatment decision tree will be proposed to guide practitioners in the management of a tooth or dental root displaced into the sinus. Conclusion: This article summarizes the importance of pre-extraction radiographic examinations for preventive purposes and their analysis to guide the practitioner in the choice of an appropriate surgical technique. Furthermore, the surgical management in almost all cases must be carried out early to prevent later infectious complications.